DETERMINAN PEMBIAYAAN MUDHARABAH PADA PT BCA SYARIAH - Arisa Agustina; Muhammad Salman; Ainul Yusna Harahap (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2023)
The research aims to determine the effect of third party funds, capital adequacy ratio and return on assets on mudharabah financing. This type of research is quantitative. The research population and sample is the annual financial report of PT BCA Syariah for 2013-2022. The data analysis method used is the classical assumption test and multiple linear analysis using SPSS as an analysis tool. The results of this study show that partially Third Party Funds (DPK) and Capital Adequacy Ratio (CAR) have a positive and significant effect on mudharabah financing and Return On Assets (ROA) has no effect on mudharabah financing. Meanwhile, simultaneously, all independent variables, namely third party funds, capital adequacy ratio and return on assets together have a significant positive influence on mudharabah financing. This research still has limitations, especially the variables studied. Further research is suggested to add other independent variables to explain their effect on mudharabah financing such as Non-Performing Financing, To Deposit Ratio, and Inflation. In addition, it is also necessary to expand the research object to include more and increase the research period so that it is hoped that better and more accurate research results will be obtained.